Special Considerations for the Treatment of Pain from Torture and War - de C Williams, Amanda C. (Curr Anesthesiol Rep, 2016)
Pain care for survivors of torture and of war shows similarities and marked differences. For both, pain can be complex with unfamiliar presentations and the pains hard to assign to known disorders. For many survivors, pain and associated disability are overshadowed by psychological distress, often by post-traumatic stress symptoms that can be frightening and isolating. Pain medicine in war can exemplify best techniques and organisation, reducing suffering, but many military veterans have persistent pain that undermines their readjustment. By contrast, survivors of torture rarely have any acute health care; their risk for developing chronic pain is high. Even when settled as refugees in a well-resourced country, their access to healthcare may be restricted. Recent evidence is reviewed that informs assessment and treatment of pain in both groups, with the broader context of psychological distress addressed at the end. Clinical and research implications are briefly outlined.